Comparison of meat quality and glycolysis potential of two hybrid pigs in three-way hybrid model - Li, Yongxiang; He, Yang; Ran, Jinming; Huang, Ying; Li, Xian; Jiang, Hengxin; Li, Xueyan; Pan, Yangsu; Zhao, Sumei; Song, Chunlian; Pan, Hongbin; Hu, Hong (Frontiers in Veterinary Science, 2023)
With the improvement of consumers' requirements for pork quality, the method of crossbreeding with excellent local pig breeds to improve meat quality is popular. Saba pig has high reproduction rate, good meat quality and high utilization rate of roughage, but its excellent characteristics have not been fully developed and utilized. To promote the development and utilization of Saba pigs and production of high-quality pork, the meat quality traits and glycolysis potential of Duroc × (Landrace × Yorkshire) (DLY), Berkshire × (Duroc × Saba) (BDS), and Duroc × (Berkshire × Saba) (DBS) three-way crossbred pigs were compared. The results showed that DLY had the highest live weight, carcass weight, lean meat percentage, drip loss, glycolysis potential, muscle diameter, and relative mRNA expression levels of type IIb muscle fibers as well as the lowest ultimate pH (p < 0.05). The lightness value of DBS was the highest (p < 0.05). Among the three crossbred pigs, myristic, arachidic, palmitoleic, and eicosenoic acids were the highest in BDS. These results indicated that the carcass traits of local crossbred pigs were worse than those of DLY pigs, but meat quality was markedly higher, with BDS showing the best meat quality.